Variabel Dominan Yang Memengaruhi Perilaku Pengelolaan Keuangan Keluarga Menghadapi Dampak Pandemi Covid 19 - Eka Putri Suryantari; Ni Luh Putu Suarmi Sri Patni (Juara: Jurnal Riset Akuntansi, 2021)
The economic life of the community during the Covid 19 pandemic experienced a decline due to restrictions on community activities both on a large scale and on a micro scale. The decline in community income due to decreased economic activity, which mostly comes from the tourism sector on the island of Bali, especially for Denpasar as the provincial capital, certainly has an impact on family financial management behavior. The location of this research is in Denpasar City using quantitative methods and the analysis technique used is multiple linear regression.           The method used in this study is a survey method using online questionnaires as a tool for data collection with 65 respondents. Financial knowledge has an unstandardized beta value of 0.715 which is the highest value compared to the other three variables so that in this study financial knowledge is the dominant variable affecting family financial management behavior during the pandemic. Thus it is very important to increase knowledge about finance that is not only obtained from educational institutions. but can be obtained from family, society and from social media.